PELATIHAN MANAJEMEN ASET TETAP DAN PENYUSUTAN ASET TETAP UNTUK KEBERLANGSUNGAN USAHA PADA KOMUNITAS PETAMBAK PERINTIS DESA LONGOS SUMENEP - Ghufrony, Ahmad; Ainun, Moh. Baqir; Pitaloka, Diah Anggraeni; Harmanto, Stevan Ariputra (INTEGRITAS : Jurnal Pengabdian, 2024)
Fixed assets are assets that a company definitely needs to run its business. Recording the acquisition of fixed assets and calculating depreciation of fixed assets is important to do correctly. This is because recording fixed assets and depreciation charges on fixed assets will affect the company's profit and loss. If the company makes a mistake in recording and calculating depreciation of fixed assets, the resulting profit and loss calculation will also be wrong. Business owners will think that their business is making a profit, even though if the depreciation of fixed assets is recorded and calculated correctly, it is likely that the business will actually experience a loss. If this type of misinformation is left unchecked, it will have an impact on the development and sustainability of the business. Such problems occurred in the "Pioneer Farmer Community" in Longos Village, Sumenep as a service partner. Partners do not have knowledge and understanding about recording and depreciating fixed assets in accordance with accounting principles, so the profit and loss calculations carried out by partners are definitely wrong. Therefore, this service aims to increase partners' knowledge and understanding of the procedures for recording fixed assets and calculating depreciation of fixed assets through outreach and training. Service is carried out through socialization and training. In the pre-test, the score obtained was 10.72 (for partner knowledge in recording fixed assets) and 5.76 (for partner knowledge in calculating fixed asset depreciation costs). After the socialization was carried out, partner knowledge increased to 56.56 (for partner knowledge in recording fixed assets) and 51.20 (for partner knowledge in calculating fixed asset depreciation costs) during the post-test.